The Effects Of Protein And Energy Supplements On Rumen Metabolism In Sheep Fed Guinea Grass Ad Libitum - Jetana, Thongsuk (1996)

(untitled)
A series of studies based on the 4 x 4 Latin square design was conducted to determine the effects of protein [fish meal (FM) or soybean meal (SBM) ] and energy [paper pulp (PP) or com flour (CF)] supplements on sheep fed guinea grass ( 1 .7 % N content) ad libitum. The dietary treatments arranged in 2 x 2 (protein x energy) factorial were: FM+PP; FM+CF; SBM+PP and SBM+CF. Three sets of studies were carried out. They were in situ degradability of feeds; rumen fermentation pattern and microbial population and feed intakes and digestion, nutrients flow and rumen nitrogen metabolism. In the first study, in situ experiment showed that the degradation of DM, OM and N of SBM were significantly (P<0.05) higher than that of FM. The percentage losses of DM, OM, NDF, ADF and N of guinea grass were significantly (P<0.05) lower in sheep fed CF at 12 h incubation. The rates of degradation 'c' of DM, OM, NDF and ADF of guinea grass were lowest in sheep fed the highly degradable protein and carbohydrate in the rumen (SBM+CF). The rate of degradation ' c' of N of guinea grass was enhanced by the highly degradable fibre (PP). In the second study, rumen pH was significantly (P<0.05) lower at 3 h after feeding in sheep fed CF when compared to sheep fed PP supplements. Molar proportions of acetate were greater (P<0.05) for sheep fed PP than sheep fed CF. Sheep fed SBM+CF showed significantly (P<0.05) higher ammonia-N concentration at 0 and 9 h after the onset of feeding when compared to sheep fed other diets. The concentrations of ammonia-N were significantly (P<0.05) higher in animals fed SBM supplements. The numbers of protozoal counts of rumen fluids were significantly (P<0.05) lower in animals fed FM+PP when compared to sheep fed other diets. The number of viable bacteria tended to be high (P<0.07) in sheep supplemented with FM when compared to sheep fed other diets.